EDUKASI SINEMA GIZI DAN CEGAH STUNTING ITU PENTING BERBASIS APLIKASI INZTING (IKHTIAR MENZEROKAN STUNTING) DI KELURAHAN PALLANTIKANG - Arafah, Salmah; Oktaviana, Dina; Sadli, Adi; Patmawati, Patmawati; Sumarmi, Sumarmi; Chaerunnisa, Putri; Husnadya, Nur; Qalbi, Nur; Arfah, Zulfikar; Kamriana, Kamriana; Suardi, Suardi (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Stunting is a condition of failure to grow in children resulting from malnutrition so that they are too short or do not grow according to their age. This is what causes stunting to become a problem that needs a solution. The aim of this PKM activity is to increase the knowledge of mothers who have stunted children and the knowledge of posyandu cadres and health cadres regarding the use of the INZTING application (Efforts to Reduce Stunting) to carry out comprehensive recording, monitoring and documentation in efforts to prevent stunting. The method for implementing this service is application-based education. The targets for this service are mothers who have 23 stunted children and 28 cadres. The evaluation instruments are pre test, post test and activeness during the activity. The analysis technique to determine the success of the activity is by looking at the comparison of the pretest and posttest results that have been given. The results of the service showed that there was an increase in mothers' knowledge about stunting, namely from 52% to 90% and of posyandu cadres regarding the use of the INZTING application, namely from 40% to 95%. Some of the material that partners have understood includes guidelines for balanced nutrition, the characteristics of stunting, and the causes of stunting in relation to nutrition, as well as the long-term impacts of stunting cases. This means that the implications of this PKM activity have been able to increase mothers' knowledge about stunting and cadres' knowledge about using the INZTING application.